Implementasi Kurikulum Merdeka melalui Integrasi CP, TP, dan ATP dalam Meningkatkan Kualitas Pembelajaran dan Profesionalisme Guru - Irda Rahmadhani; Hasanah Hasanah; Evina Putri Fernanda; Nineteen Uchi Ray Simanjuntak; Jelfrida Malau (Pusat riset dan Inovasi Nasional, 2025)
This study discusses the implementation of the Self-Directed Learning Programme by integrating Learning Outcomes (CP), Learning Objectives (TP), and Learning Objective Processes (ATP) to enhance teaching quality and teacher professionalism. Using a library research method, this study analyses relevant scientific literature to understand the relationship between the integration of the three components of the education programme and classroom teaching practices. The research findings indicate that teachers still encounter challenges in understanding and integrating CP, TP, and ATP, particularly in planning, implementing teaching strategies, and conducting authentic assessments. However, when this integration is well executed, the teaching process becomes more purposeful, flexible and responsive to students' needs. Furthermore, integrating CP–TP–ATP has been shown to strengthen teachers' professionalism by enhancing their understanding of the curriculum, their ability to design learning activities, and their capacity to conduct competency-based assessment. This study confirms that the successful implementation of the Free Education Programme depends heavily on teachers' ability to understand the curriculum's structure and to integrate these three components consistently. Therefore, training, supporting, and developing teachers' competencies is an important requirement for the effective and sustainable implementation of the Liberal Education Programme.